The effects of acute and chronic administration of phosphatidylserine on cell proliferation and survival in the dentate gyms of adult and middle-aged rats - Maragno, Heloisa; Rodella, Patricia [UNESP]; Freitas, Josiane da Silva; Takase, Luiz Fernando (Elsevier B.V., 2015)
Phosphatidylserine (PS) is an acidic phospholipid that is widely used as an alternative and/or complementary treatment of cognitive impairments. We hypothesize that these changes may be attributable, at least in part, to alterations in hippocampal neurogenesis. The aim of the present study was to investigate the effects of acute and chronic PS administration on hippocampal cell proliferation and survival in adult (5 months old) and middle-aged (12 months old) male Wistar rats. PS was injected daily (50 mg/kg, i.p.) during 7 days (acute experiment) or 21 days (chronic experiment). To label newly generated cells, rats received a single BrdU injection (200 mg/kg, i.p.) one day before PS treatment. The object recognition test was performed, and the rats were perfused. The brains were removed and processed with immunohistochemistry techniques for Ki-67 (cell proliferation) and BrdU (cell survival). The acute and chronic regimens were unable to promote cognitive improvement in either age group in the object recognition test. The analysis of cell proliferation showed a significant increase in the number of Ki-67-positive cells after acute and chronic PS administration in both age groups. The analysis of cell survival showed that acute and chronic PS administration increased the number of BrdU-positive cells only in adult animals.
Keywords: Phosphatidylserine; Neurogenesis; BrdU; Ki-67; Object recognition test; Aging